Evaluation of public actions on food environments to combat the double burden of malnutrition in Benin using the Food-EPI tool - Santos , Reynald; Sossa Jerome, Charles; Azandjeme , Colette; Metonnou, Clémence; Soliba Manga, Julien; Vandevijvere, Stefanie; Moubarac, Jean-claude; Diouf, Adama (Progress in Nutrition, 2024)
Background and aim: Despite national policies and food-related interventions, Benin still faces a number of nutritional problems. The food environment, which is crucial to health, receives little attention in food policies. Monitoring food environments is essential to combat the double burden of malnutrition (DBM). The objective was to assess the level of implementation of public policies and government actions aimed at creating healthy food environments in BENIN. Methods: The evaluation was carried out using the INFORMAS Food-EPI module. Initially, the module contained 47 indicators relating to the prevention of obesity and diet-related non-communicable diseases. This tool was initially adapted to the Benin context. Following its implementation in sub-Saharan Africa (Ghana, Kenya and Senegal), 12 new indicators were added to make the Food-EPI tool more sensitive to the DBM. A group of independent experts (n=22) and government experts (n=21) assessed the level of the implementation of public policies using a Likert scale and identified the priority actions. Results: Of the 59 indicators compiled from 61 policy documents, the implementation level of public policies was assessed as "very low" for 27 indicators, "low" for 24 indicators and "medium" for 8 indicators. The inter-rater reliability index was estimated at 0.94 (CI: 0.92-0.97) and considered good. The experts identified 116 actions, 10 of which were prioritized in terms of importance, achievability and effect on the DBM, and recommended to the Beninese government. In the "Policy" component, priority actions focused mainly on food promotion, supply, pricing and retailing. In the "Infrastructure Support" component, priority actions focused on governance, leadership, monitoring and evaluation. Conclusions: This study proposes a list of priority actions to the government to transform the food environments towards reducing the DBM in Benin.